Association of loneliness and social network size in adulthood with childhood maltreatment: Analyses of a population-based and a clinical sample - Matthias A. Reinhard; Stephanie V. Rek; Tabea Nenov-Matt; Barbara B. Barton; Julia Dewald-Kaufmann; Katharina Merz; Richard Musil; Andrea Jobst; Eva-Lotta Brakemeier; Katja Bertsch; Frank Padberg (European Psychiatry, 2022)
Abstract